Spatial Differentiation of Energy Poverty in Eu Countries. (June 2018) - Zawada, M; Szajt, M; Kowalik, J; Kucęba, R
Abstract: The provision of heat and electricity in the household is one of the basic human needs. However, many households are experiencing energy poverty, so it is difficult to satisfy basic energy needs. These households have to choose between drastic energy savings, which results in experiencing lack of thermal comfort and energy expenditure at the expense of other basic needs, such as food or health. The main aim of this article is to analyse the state of energy poverty in the European Union countries by comparing the basic characteristics of its measurement such as: income, energy consumption, energy prices in the years 2006-2015. This allowed to indicate the existence of spatial variations between members of the European Union.